2022
DOI: 10.4322/ahns.2022.0005
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the anterior jugular veins: anatomical study of 30 cadavers

Abstract: Introduction: Human anatomy is essential for both clinical and surgical practice. Although the anterior jugular veins (AJVs) are of great importance in many surgeries, there are few studies addressing the anatomic variations of these vessels. This study highlights the venous drainage of the head and neck and the importance of anatomical variations in the AJVs. Objective: To observe and describe the anatomy of the jugular veins and evaluate whether there are patterns influenced by anthropometric factors or como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, the right IJV had a larger than normal diameter above the cricoid cartilage, and the left IJV had a smaller than normal diameter (Table 1). Hojaij et al reported that the AJV's diameter was ≥ 5 mm in 40% of 30 cadavers studied; however, the AJV is typically smaller than the other jugular veins [2,10]. In this case, the left AJV was larger than the other jugular veins on the left (Table 1) which was likely due to its communication with the other veins.…”
Section: Discussionmentioning
confidence: 75%
“…However, the right IJV had a larger than normal diameter above the cricoid cartilage, and the left IJV had a smaller than normal diameter (Table 1). Hojaij et al reported that the AJV's diameter was ≥ 5 mm in 40% of 30 cadavers studied; however, the AJV is typically smaller than the other jugular veins [2,10]. In this case, the left AJV was larger than the other jugular veins on the left (Table 1) which was likely due to its communication with the other veins.…”
Section: Discussionmentioning
confidence: 75%